DERMATOGLYPHIC PATTERNS OF LONG-TAILED MONKEY POPULATION AT BUKIT GUMANG TEMPLE, KARANGASEM, BALI - Ni Putu Premasuari Putri Maha Devi; I Gede Soma; I Nengah Wandia (Buletin Veteriner Udayana, 2025)
Macaca fascicularis (long-tailed monkey) is one of the primates that is widely distributed. The population of long-tailed monkeys on the island of Bali can be found at 43 points, one of which is in Pura Bukit Gumang, Pekraman Bugbug, Karangasem district. Different populations can have different variations of dermatoglyphic patterns, therefore this study was conducted to determine the dermatoglyphic pattern and the highest frequency of the type of fingerprint pattern of long-tailed monkeys in Pura Bukit Gumang Karangasem Bali. The study used 13 samples of dermatoglyphics of the hands and feet of long-tailed monkeys in Pura Bukit Gumang Karangasem Bali. Dermatoglyphic impressions were taken using transparent adhesive plastic that had been given graphite powder on the palms and feet of long-tailed monkeys. The results of the study found 4 basic dermatoglyphic patterns, namely open field (47%), whorl (31%), loop (20%) and arch (2%). The highest frequency of dermatoglyphic patterns of the palms of long-tailed monkeys was whorl 37.9% and the highest frequency of dermatoglyphic patterns of the soles of the feet was open field (57.3%). Open field is the highest frequency of all palm and foot pattern areas with a percentage of 47%. The research that has been done is still limited by the number of samples. To improve the accuracy of dermatoglyphic patterns in monkey populations, it is recommended to use more representative samples for the population.